Pouvoir et légitimité des figures de l’Etat au Chili de 1810 à 1861 - Nathalie Jammet (Les Cahiers ALHIM)
This article aims at showing how the State’s authority was constituted in Chile between 1810 and 1861. First, the political leaders took emergency measures so as to fit the exceptional context. At this time, it was a necessity to ensure the political independence by creating a regular army and by nominating some new representatives in the different regions. It was also necessary to justify the movement to independence by ending with the colonial spirit. The equality of anyone to the law, which used to be a widespread ideal, motivated a re-organisation of the judicial power. Despite these first attempts to settle new administrative structures, the development of the State was really implemented only after 1830, thanks to the initiative of the Minister Diego Portales. Three priorities were then chosen: guaranteeing the Peace inside the borders by furthering the revolted leaders and creating new military forces; developing the administrative structures thanks to the early adoption of a policy of rationalization; and elaborating some judiciary procedures. Thanks to this normative effort that became obvious during the «Authoritarian Republic», the administrative structures, that were necessary so as to comfort the authority of the State, had already been settled in Chile since 1861.